Equivalence Trial of the Non-Bismuth 10-Day Concomitant and 14-Day Hybrid Therapies for Helicobacter pylori Eradication in High Clarithromycin Resistance Areas - Sotirios D. Georgopoulos; Elias Xirouchakis; Christos Liatsos; Pericles Apostolopoulos; Panagiotis Kasapidis; Beatriz Martinez-Gonzalez; Fotini Laoudi; Maria Stoupaki; Georgios Axiaris; Dionysios Sgouras; Andreas Mentis; Spyridon Michopoulos (MDPI AG, 2024)
Background and aim: We conducted an equivalence trial of quadruple non-bismuth "concomitant" and "hybrid" regimens for H. pylori eradication in a high clarithromycin resistance area. Methods: There were 321 treatment-naïve H. pylori-positive individuals in this multicenter clinical trial randomized to either the hybrid (esomeprazole 40 mg/bid, amoxicillin 1 g/bid for 7 days, then 7 days esomeprazole 40 mg/bid, amoxicillin 1 g/bid, clarithromycin 500 mg/bid, and metronidazole 500 mg/bid) or the concomitant regimen (all medications given concurrently bid for 10 days). Eradication was tested using histology and/or a 13C-urea breath test. Results: The concomitant regimen had 161 patients (90F/71M, mean 54.5 years, 26.7% smokers, 30.4% ulcer) and the hybrid regimen had 160 (80F/80M, mean 52.8 years, 35.6% smokers, 31.2% ulcer). The regimens were equivalent, by intention to treat 85% and 81.8%, (p = 0.5), and per protocol analysis 91.8% and 87.8%, (p = 0.3), respectively. The eradication rate by resistance, between concomitant and hybrid regimens, was in susceptible strains (97% and 97%, p = 0.6), clarithromycin single-resistant strains (86% and 90%, p = 0.9), metronidazole single-resistant strains (96% and 81%, p = 0.1), and dual-resistant strains (70% and 53%, p = 0.5). The side effects were comparable, except for diarrhea being more frequent in the concomitant regimen. Conclusions: A 14-day hybrid regimen is equivalent to a 10-day concomitant regimen currently used in high clarithromycin and metronidazole resistance areas. Both regimens are well tolerated and safe.